2022
DOI: 10.1186/s12891-022-05874-w
|View full text |Cite
|
Sign up to set email alerts
|

The influence of obesity on functional outcomes and patient satisfaction 8 weeks after total knee arthroplasty: results of the prospective FInGK study

Abstract: Objectives To investigate obese versus non-obese subjects´ knee joint function, stiffness, pain, expectations, and outcome satisfaction before and two months after total knee arthroplasty (TKA). Methods This study is a secondary analysis of data retrieved via a prospective single-centre cohort study investigating knee joint function and health care services utilization in patients undergoing TKA (FInGK Study). For the primary study, elective TKA pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Very few studies have investigated the relationship between BMI and the outcomes of MPFL reconstruction. Studies analysing other surgical procedures such as knee arthroplasty has found obesity is associated with lower postoperative outcomes scores [3,19,25], treatment satisfaction and impaired health-related QoL [3,19] The results of this study build upon those reported by Enderlein et al [8], who found that postoperative clinical outcomes of MPFL reconstruction were inferior in patients with a BMI > 30 kg/m 2 . When we analysed the same two BMI groups in our study, we found that surgery gave both groups an almost identical mean improvement of around 23 and 26 points on the Kujala and IKDC scales.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Very few studies have investigated the relationship between BMI and the outcomes of MPFL reconstruction. Studies analysing other surgical procedures such as knee arthroplasty has found obesity is associated with lower postoperative outcomes scores [3,19,25], treatment satisfaction and impaired health-related QoL [3,19] The results of this study build upon those reported by Enderlein et al [8], who found that postoperative clinical outcomes of MPFL reconstruction were inferior in patients with a BMI > 30 kg/m 2 . When we analysed the same two BMI groups in our study, we found that surgery gave both groups an almost identical mean improvement of around 23 and 26 points on the Kujala and IKDC scales.…”
Section: Discussionsupporting
confidence: 70%
“…Very few studies have investigated the relationship between BMI and the outcomes of MPFL reconstruction. Studies analysing other surgical procedures such as knee arthroplasty has found obesity is associated with lower postoperative outcomes scores [3, 19, 25], treatment satisfaction and impaired health‐related QoL [3, 19]…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of obesity on patient-reported outcomes remains unclear. Although some studies reported no association, others reported either negative or positive associations between obesity and postoperative pain and functional outcomes [ 16 , 18 , 19 , 20 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Previous studies have mainly focused on mid- to long-term outcomes, with limited evidence on the early recovery phase [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies reported no association, others reported either negative or positive associations between obesity and postoperative pain and functional outcomes [ 16 , 18 , 19 , 20 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Previous studies have mainly focused on mid- to long-term outcomes, with limited evidence on the early recovery phase [ 30 ]. Furthermore, most studies investigating this association have been conducted in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis is a degenerative disease of the joints that cause joint pain, stiffness, swelling, restricted movement and even joint deformity. Osteoarthritis of the knee is the most common type of osteoarthritis, with 360 million cases worldwide each year [ 1 ]. When knee osteoarthritis progresses to the end stage, total knee arthroplasty (TKA) is an effective and commonly used treatment modality.…”
Section: Introductionmentioning
confidence: 99%